PUASA DALĀIL AL-QUR’ĀN: DASAR DAN MOTIVASI PELAKSANAANNYA - Muhammad Abdul Kharis; Alvin Noor Sahab Rizal (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
Darul Falah Islamic Boarding School Jekulo Kudus, one of the Boarding School that encourages every student to sunnah fasting. Various kinds of sunnah fasting that are familiar in society, such as Monday-Thursday fasting, Daud fasting, and Nyirih fasting. Dalā’il fasting known as the sunnah fasting, which is less familiar among the people. Dalā’il fasting is divided into the fasting of Dalā’il al-Khairāt and Dalā’il al-Qurān. The fasting of Dalā’il al-Qurān is fasting that implemented for one full year by reading one juz al-Qur’an every day. Based on the understanding of Dalā’il al-Qurān fast, then this fast falls into the category of dahr fast. Many arguments are used to explain the prohibition on dahr fasting. However, if the hadith is understood in terms of asbābul wurud, then this kind of fasting may be done. The existence of the hadith which prohibits doing dahr fasting is based on the advice of the Rasulullah to ‘Abd Allāh bin ‘Amr.